A174 RARE BUT DEADLY: AN APPROACH TO MANAGEMENT OF DUODENAL VARICEAL HEMORRHAGE. (26th February 2020) - Dahiya, M; Tomaszewski, M; Ou, G; Ramji, A
Abstract: Background: Common etiologies of upper gastrointestinal bleeding (UGIB) in cirrhotic patients with portal hypertension include gastroesophageal varices (GOV), portal hypertensive gastropathy (PHG) and gastric antral vascular ectasia (GAVE). Less commonly, patients with portal hypertension develop varices in ectopic sites, including the rectum, biliary tree and duodenum. Ectopic varices are rare, contributing to 1–5% of all variceal bleeding, of which 17% is from duodenal varices. Aims: To describe the management of duodenal variceal hemorrhage. Methods: A case report and literature review was performed. Results: Case report: We present a case of recurrent UGIB in a 59-year-old male with decompensated cirrhosis due to non-alcoholic steatohepatitis (CP-C; Meld 14). Initial endoscopy was negative for GOV, peptic ulcer, PHG, and GAVE, but an erosion over a mucosal bulge in the third segment of the duodenum was identified, raising possibility of vascular malformation versus ectopic varix. There was active bleeding after water provocation, so clips were deployed for hemostasis. CT imaging showed mesenteric venous collaterals abutting the duodenum, again raising possibility of duodenal varix, which was ultimately confirmed by endoscopic ultrasound (EUS). Patient had recurrent overt bleeding despite beta-blockage for prophylaxis, endoscopic clipping on four separate occasions, attempted angioembolization by interventional radiology, and cyanoacrylate glue. Transjugular intrahepatic porto-systemic shunt (TIPS) was not possible due to portal vein occlusion, so he underwent EUS-guided cyanoacrylate glue a second time. Literature review: Ectopic varices are rare, contributing to 1–5% of all variceal bleeding, of which 17% is from duodenal varices. Duodenal variceal hemorrhage can lead to hemorrhagic shock, and is potentially life threatening, with quoted mortality rates of 40%. Unfortunately, duodenal varices can be difficult to identify. Diagnosis is often delayed due to a combination of lower awareness and endoscopic challenges given the unusual serosal and submucosal location. Evidence-based guidelines for the management of ectopic varices are limited. For this reason, our current management strategies rely heavily on local expertise. Splanchnic vasoconstrictor medication, endoscopic ligation, EUS guided gluing, interventional radiology guided embolization, TIPS, balloon retrograde transvenous obliteration and surgical shunts are potential therapeutic options to manage the acutely bleeding varix. Following a variceal bleed, liver transplantation should be considered in eligible patients with no other contraindications. Conclusions: Duodenal varices are a rare, potentially fatal, and underrecognized cause of gastrointestinal bleeding in patients with portal hypertension. Definitive therapy currently relies upon local expertise in the absence of clear guideline-based therapy. Funding Agencies: None